Joint ventures in the Flag Boshielo Irrigation Scheme, South Africa: a history of smallholders, states and business - van Koppen, Barbara; Tapela, B.N.; Mapedza, Everisto D. (International Water Management Institute, 2018)
The report analyzes the changing tripartite constellations between South African black smallholders, the pre- and post-apartheid state, and the country’s large-scale agribusiness and irrigation industry. A recent mode of farming is the ‘joint venture’, in which smallholders hand over land and share in the net profits, while a strategic partner manages the cultivation with own inputs and equipment, and markets the output. With a focus on the 13 sub-schemes of the Flag Boshielo irrigation scheme in the former homeland of Lebowa (current Limpopo Province), the report analyzes the emergence of six joint ventures - the collapse of three and the troubled continuation of the other three. For the government’s support to joint ventures as one of the options of the revitalization of smallholder irrigation schemes in former homelands, it is recommended to ensure there is a robust bilateral contract between smallholders and the strategic partner, to strengthen land tenure arrangements, and to diversify irrigation technologies for women and men smallholders.